Analysis of coverage probability in NOMA-HetNet based on Matern cluster process - Xiaorong JING; Yixi CHEN; Qianbin CHEN (Tongxin xuebao)
Considering the correlation between the users and base stations and the network irregularity,the non-orthogonal multiple access heterogeneous networks (NOMA-HetNet) based on Matern cluster process (MCP) was modeled.The coverage probability of UEs was analyzed.Firstly,the signal-to-interference-plus-noise ratios (SINR) of UEs were theoretically derived.Secondly,an updating law for the upper limit of SINR was presented for the imperfect serial interference elimination (SIC) scheme,which was more consistent with the reality.Then,using the mathematical tools such as spatial coordinate system,probability theory,stochastic geometry theory and order statistics,the correlation probability and service distances of the different types of UEs were analyzed.Finally,the theoretical expression of the coverage probability of UEs was derived.The effects of cluster radius,base station density,interference residual factors on service distances,and coverage probability are verified by numerical simulations.The simulation results are consistent with the theoretical analysis,which testifies the correctness of the theoretical analysis.